Synthesis, characterization and binding studies of dieldrin, endosulfan, hexachlorobenzene imprinted polymers using gas chromatography-ECD and dye displacement method - OFELIA, SILVERIO (Archīum Ateneo, 2016)
In this paper, molecularly imprinted polymers (MIPs) were prepared usingthree different organochlorine pesticide templates: dieldrin, endosulfan andhexachlorobenzene. Optimization of different synthesis parameters showed that thethree MIPs prepared using